Rituximab in Antimelanoma Differentiation-Associated Protein-5 Dermatomyositis with Interstitial Lung Disease. (30th May 2020) - Scirocco, Chiara; Gubbiotti, Andreina; Sebastiani, Alfredo; Sebastiani, Gian Domenico
Abstract : In this paper, we report a challenging case of a middle-age woman who developed antimelanoma differentiation-associated protein-5 dermatomyositis (anti-MDA5 DM) with interstitial lung disease (ILD) and was successfully treated with rituximab (RTX), after failure of a first-line therapy.